Cesarean Section followed by myomectomy in a pregnancy complicated by left intraligamentous myoma (Faculty of Medicine Universitas Indonesia, 2004)
A 20-year-old primigravida with 38th weeks of gestation complicated with a left large solid intraligamentous uterine tumor. The operation started with lower segment cesarean section to delivere the fetus. Intramural uterotonica was given and the uterus contracted well; intra- and up to 24 hours post-operatively oxytocin infusion was administered. Double circle stitching technique was performed on lateral side of the mioma before starting myomectomy. No blood transfusion was given. The histopatological report was leiomyoma. She was discharged in healthy condition 4 days post-operatively. (Med J Indones 2004; 13: 66-8) Keywords: Myomectomy, cesarean section, intraligamentous myoma